Risk factors of hospitalization for carpal tunnel syndrome among the general working population - Hulkkonen, Sina; Shiri, Rahman; Auvinen, Juha; Miettunen, Jouko; Karppinen, Jaro; Ryhänen, Jorma (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'Carpal tunnel syndrome (CTS) causes a considerable amount of sick leave and healthcare costs. The etiology of CTS is multifactorial, involving both personal and occupational risk factors. To date, few prospective cohort studies on occupational risk factors of CTS have examined the general working population. ' ' METHODS ': 'The study population consisted of participants from the Northern Finland Birth Cohort of 1966 who attended the 31-year follow-up in 1997 and were working ≥3 days a week in a paid job (N=6326). Information on socio-economic status, weight and height, smoking, exposure to occupational physical factors, and long-term illnesses was collected at baseline in 1997. Data on hospitalizations due to CTS came from the Care Register for Health Care, 1997–2016. ' ' RESULTS ': 'Between 1997 and 2016, 3.4% of the participants had been hospitalized (attended secondary care) for CTS. After adjusting for confounders, women [hazard ratio (HR) 3.77, 95% confidence interval (CI) 2.70–5.25], overweight/obese participants (HR 1.69, 95% CI 1.29–2.22), smokers (HR 1.48, 95% CI 1.12–1.96), farmers and manual workers (HR 3.02, 95% CI 1.85–4.92 compared with upper clerical workers), lower clerical workers (HR 1.74, 95% CI=1.08–2.80), workers exposed to hand vibration (HR 2.29, 95% CI 1.48–3.54) and participants with physically demanding jobs (HR 1.71, CI 1.06–2.76) were at increased risk of hospitalization for CTS. Physically demanding work increased the risk of hospitalization for CTS for overweight/obese participants at baseline, but not for participants of normal weight. ' ' CONCLUSIONS ': 'Excess body mass and occupational physical factors increase the risk of hospitalization for CTS. Excess body mass potentiates the adverse effects of strenuous work on CTS.
Keywords: carpal tunnel syndrome; cohort study; CTS; Finland; hospitalization; median nerve; musculoskeletal disorder; occupational exposure; overweight; risk factor; working population